2019
DOI: 10.1097/acm.0000000000002905
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of Honors: A Multi-Institutional Study of Students’ Perceptions of Clerkship Evaluation and Grading

Abstract: Purpose To examine medical students’ perceptions of the fairness and accuracy of core clerkship assessment, the clerkship learning environment, and contributors to students’ achievement. Method Fourth-year medical students at 6 institutions completed a survey in 2018 assessing perceptions of the fairness and accuracy of clerkship evaluation and grading, the learning environment including clerkship goal structures (mastery- or performance-oriented), raci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Whether or not an institution openly acknowledges the predictable need for remediation and works to destigmatize and adequately resource remediation in medical education is a reflection of the culture of that institution [37]. Medical education programs have traditionally used deficit-based approaches to education, which can encourage learners to focus on surface performance rather than deeper understanding to avoid negative labels [38]. More recently, programs have increased adoption of competency-based approaches, which de-emphasize time spent in training and emphasize the developmental, possibly time-variable, nature of the acquisition of capacities [39].…”
Section: Results (Tab 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not an institution openly acknowledges the predictable need for remediation and works to destigmatize and adequately resource remediation in medical education is a reflection of the culture of that institution [37]. Medical education programs have traditionally used deficit-based approaches to education, which can encourage learners to focus on surface performance rather than deeper understanding to avoid negative labels [38]. More recently, programs have increased adoption of competency-based approaches, which de-emphasize time spent in training and emphasize the developmental, possibly time-variable, nature of the acquisition of capacities [39].…”
Section: Results (Tab 2)mentioning
confidence: 99%
“…Many stressors, particularly those fostered by the implicit curriculum, can influence the need for future remediation. Students report feeling that they are constantly being evaluated, particularly in the setting of clerkships where the criteria and expectations for grades are subjective and appear arbitrary and whimsical [38, 72, 73]. A strategy shown to have potential to alleviate some of that stress is the facilitated support group with sessions aimed at increasing self-awareness, self-care, and/or mindfulness training [7476].…”
Section: Results (Tab 2)mentioning
confidence: 99%
“…The learning environment also has implications for professional development and career choice. Students from URM groups have reported experiencing discrimination at greater rates, 13 , 26 and studies have found racial disparities in clerkship grades 27 , 28 , 29 and medical student evaluations. 30 Stereotype threat (ie, fear of confirming a primarily negative perception about one’s racial, ethnic, or other social group), which is prevalent among Asian and Black students, 31 is more likely to occur in less diverse settings, with consequences for performance, grading, and effective educational alliances.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of medical students during clerkships is largely driven by clinical performance ratings, but many students perceive clinical evaluations to be “unfair” and call for more training of evaluators. 1 Limitations in self-assessment may contribute to this perception, 2 and frame-of-reference training may improve students’ ability to recognize different levels of performance. 3 The objective of this study was to determine if an online, frame-of-reference training module can improve students’ understanding of clerkship expectations for clinical performance in the medicine clerkship.…”
Section: Purposementioning
confidence: 99%